Level Scheme of 102In first observed - Adamides, E.; Seweryniak, D.; Cederwal, B.; Nyberg, J.; Fahlander, C.; Jonson, A.; Kerek, A.; Kownacki, J.; Norlin, L-O.; Atac, A.; Blomqvist, J.; Grawe, H.; et al. (HNPS Advances in Nuclear Physics, 2019)
Neutron deficient nuclei close to 100Sn have been investigated in-beam by particle and γ-ray spectroscopic methods using the NORDBALL detector array following the bombartment of a 54Fe target with a beam of 270 MeV 58Ni. Protons and α particles were identified with a 4π ΔΕ-type Si-multidetector and neutrons with a 1π liquid-scintillator-detectorassembly placed in the forward derection. Excited states of 102In were identified for the first time. The level scheme constructed from γ-γ-particle-coincidence and γ angular correlations is discussed and compared to the structure of neighboring nuclei in the framework of the nuclear shell model.